Enhancing Employee Performance: The Impact of Transformational Leadership, Motivation, and Workload: Menyempurnakan Kinerja Karyawan: Dampak Kepemimpinan Transformasional, Motivasi, dan Beban Kerja. - Rezza Baharuddin Prawibowo; Detak Prapanca (Academia Open, 2024)
This study investigates the influence of Transformational Leadership, Motivation, and Workload on employee performance in a sample of 55 respondents from the UD. Sinar Mas organization. Employing a non-probability sampling method with saturated sampling technique, the study utilizes multiple linear regression analysis to analyze the data. The findings demonstrate that Transformational Leadership, Motivation, and Workload all exert a positive and statistically significant impact on employee performance. This research underscores the importance of these factors in enhancing employee performance and provides valuable insights for organizations seeking to optimize their workforce's productivity. Highlight: This study explores the influence of Transformational Leadership, Motivation, and Workload on employee performance. Employing multiple linear regression analysis on a sample of 55 respondents, it identifies a significant positive impact of these factors on employee performance. The research offers valuable insights for organizations aiming to enhance workforce productivity. Keywords: Transformational Leadership, Motivation, Workload, Employee Performance, Saturated Sampling.